Post-discharge outcomes of hospitalized children diagnosed with acute SARS-CoV-2 or MIS-C - Fink, Ericka L.; Alcamo, Alicia M.; Lovett, Marlina; Hartman, Mary; Williams, Cydni; Garcia, Angela; Rasmussen, Lindsey; Pal, Ria; Drury, Kurt; MackDiaz, Elizabeth; Ferrazzano, Peter A.; Dervan, Leslie; et al. (Frontiers in Pediatrics, 2024)
Introduction: Hospitalized children diagnosed with SARS-CoV-2-related conditions are at risk for new or persistent symptoms and functional impairments. Our objective was to analyze post-hospital symptoms, healthcare utilization, and outcomes of children previously hospitalized and diagnosed with acute SARS-CoV-2 infection or Multisystem Inflammatory Syndrome in Children (MIS-C).Methods: Prospective, multicenter electronic survey of parents of children < 18 years of age surviving hospitalization from 12 U.S. centers between January 2020-July 2021. The primary outcome was parent report of child recovery status at the time of the survey (recovered vs. not recovered). Secondary outcomes included new or persistent symptoms, readmissions, and health-related quality of life. Multivariable backward, stepwise, logistic regression was performed for the association of patient, disease, laboratory, and treatment variables with recovered status.Results: Children (n=79; 30 [38.0%] female) with acute SARS-CoV-2 (75.7%) or MIS-C (24.3%) were median age 6.5 years (interquartile range 2.0-13.0) and 51 (64.6%) had a preexisting condition. Fifty children (63.3%) required critical care.One-third (23/79 [29.1%]) were not recovered at follow-up (43 [31, 54] months post-discharge). Admission C-reactive protein levels were higher in children not recovered versus recovered (5.7 [1.3, 25.1] vs. 1.3 [0.4, 6.3] mg/dL, p=0.02). At follow-up, 67% overall had new or persistent symptoms. The most common symptoms were fatigue (37%), weakness (25%), and headache (24%), all with frequencies higher in children not recovered. Forty percent had at least one return emergency visit and 24% had a hospital readmission. Recovered status was associated with better total HRQOL (87 [77, 95] vs. 77 [51, 83], p=0.01). In multivariable analysis, lower admission C-reactive protein (odds ratio 0.90 [95% confidence interval 0.82, 0.99]) and higher admission lymphocyte count (1.001 [1.0002, 1.002]) were associated with recovered status.Children considered recovered by their parents following hospitalization with SARS-CoV-2-related conditions had less symptom frequency and better HRQOL and CIS scores than those reported as not recovered.Increased inflammation and lower lymphocyte count on hospital admission may help to identify children needing longitudinal, multidisciplinary care.